Development of Contextual Learning Models to Improve Student's Speaking Skills - Lukman, Lukman (JOLLT Journal of Languages and Language Teaching, 2024)
An alternative solution for students to learn in a fun way is to use a contextual learning model. The contextual learning model is expected to activate the potential of teachers and students in teaching-learning interactions. Therefore, This research aims to obtain a contextual English learning model that can improve the speaking skills of junior high school students. The method used in the study is the research and development method. The results of the research produced several conclusions. First, the resulting learning model is a Contextual Learning Model, which can be used to improve students' speaking skills. The contextual English learning model developed has components including (1) establishing meaningful relationships, (2) doing meaningful work, (3) carrying out an independent learning process, (4) collaborating, (5) thinking critically and creatively, (6) ) provide individualized service, (7) strive to achieve high standards, and (8) use authentic assessment. Second, the learning design model presents learning plans and learning procedures. The main steps are exploration (apperception), consolidation, attitude formation, and closure. Third, the contextual learning model resulting from this development is efficacious in improving students' speaking skills in learning English. High effectiveness in improving speaking skills for better students with better school rankings. The developed contextual English learning model can make it easier for teachers to carry out the English language learning process in junior high schools, improve students' speaking skills, and improve contextual learning models, especially in English subjects in junior high schools.